Influence of corporate social responsibility (CSR) on safety culture = Wpływ odpowiedzialności społecznej przedsiębiorstwa (CSR) na kształtowanie kultury bezpieczeństwa - Górny, Adam (Zielona Góra: Faculty of Economics and Management Press)
Both safety culture and corporate social responsibility are essential drivers of enterprise value. By recognizing and adopting the principles of social responsibility, an organization may achieve a lasting competitive advantage on its markets.
Keywords: odpowiedzialność społeczna; zarządzanie; kultura bezpieczeństwa; przewaga konkurencyjna; social responsibility; management; safety culture; competitive advantage